Water Access and Adherence Intention Among HIV-Positive Pregnant Women and New Mothers Receiving Antiretroviral Therapy in Zambia - Nutor, Jerry John; Marquez, Shannon; Slaughter-Acey, Jaime C.; Hoffmann, Thomas J.; DiMaria-Ghalili, Rose Ann; Momplaisir, Florence; Opong, Emmanuel; Jemmott, Loretta Sweet (Frontiers in Public Health, 2022)
Background: Mother-to-infant transmission of HIV is a major problem in sub-Saharan Africa despite free or subsidized antiretroviral treatment (ART), but is significantly reduced when mothers adhere to ART. Because potable water access is limited in low-resource countries, we investigated water access and ART adherence intention among HIV-positive pregnant women and new mothers in Zambia. Methods: Our convenience sample consisted of 150 pregnant or postpartum women receiving ART. Descriptive statistics compared type of water access by low and high levels of ART adherence intention. Results: Most (71%) had access to piped water, but 36% of the low-adherence intention group obtained water from a well, borehole, lake or stream, compared to only 22% of the high-adherence intention group. The low-adherence intention group was more rural (62%) than urban (38%) women but not statistically significant (unadjusted Prevalence Ratio (PR) 0.73, 95% CI: 0.52-1.02; adjusted PR 1.06, 95% CI: 0.78-1.45). Conclusion: Providing potable water may improve ART adherence. Assessing available water sources in both rural and urban locations is critical when educating women initiating ART.